INtervention for Cognitive Reserve Enhancement in delaying the onset of Alzheimer’s Symptomatic Expression (INCREASE), a randomized controlled trial: rationale, study design, and protocol - Moga, Daniela C. (Trials, 2019)
BACKGROUND: The course of Alzheimer’s disease (AD) includes a 10–20-year preclinical period with progressive accumulation of amyloid β (Aβ) plaques and neurofibrillary tangles in the absence of symptomatic cognitive or functional decline. The duration of this preclinical stage in part depends on the rate of pathologic progression, which is offset by compensatory mechanisms, referred to as cognitive reserve (CR). Comorbid medical conditions, psychosocial stressors, and inappropriate medication use may lower CR, hastening the onset of symptomatic AD. Here, we describe a randomized controlled trial (RCT) designed to test the efficacy of a medication therapy management (MTM) intervention to reduce inappropriate medication use, bolster cognitive reserve, and ultimately delay symptomatic AD. METHODS/DESIGN: Our study aims to enroll 90 non-demented community-dwelling adults ≥ 65 years of age. Participants will undergo positron emission tomography (PET) scans, measuring Aβ levels using standardized uptake value ratios (SUVr). Participants will be randomly assigned to MTM intervention or control, stratified by Aβ levels, and followed for 12 months via in-person and telephone visits. Outcomes of interest include: (1) medication appropriateness (measured with the Medication Appropriateness Index (MAI)); (2) scores from Trail Making Test B (TMTB), Montreal Cognitive Assessment (MoCA), and California Verbal Learning Test (CVLT); (3) perceived health status (measured with the SF-36). We will also evaluate pre- to post-intervention change in: (1) use of inappropriate medications as measured by MAI; 2) CR Change Score (CRCS), defined as the difference in scopolamine-challenged vs unchallenged cognitive scores at baseline and follow-up. Baseline Aβ SUVr will be used to examine the relative impact of preclinical AD (pAD) pathology on CRCS, as well as the interplay of amyloid burden with inappropriate medication use. DISCUSSION: This manuscript describes the protocol of INCREASE (“INtervention for Cognitive Reserve Enhancement in delaying the onset of Alzheimer’s Symptomatic Expression”): a randomized controlled trial that investigates the impact of deprescribing inappropriate medications and optimizing medication regimens on potentially delaying the onset of symptomatic AD and AD-related dementias. TRIAL REGISTRATION: ClinicalTrials.gov, NCT02849639. Registered on 29 July 2016.